Agreement restrictions in Persian - Sedighi, Anousha, 1973- (Silsilat al-dirāsāt al-Īrānīyah., 2010)
"Agreement restrictions in Persian" is the first comprehensive attempt to tackle the issue of verbal agreement in Persian from a cross-linguistic point of view. Persian is a field of research within theoretical linguistics that is yet to be sufficiently explored. This book adopts the Minimalist Program of Chomsky (1995-2004) which is at the forefront of recent theories of formal syntax and applies it to the Persian language